PENGGUNAAN MEDIA CELEMEK BERCERITA DALAM MENSTIMULASI ANAK SPEECH DELAY - Mastikawati; Azwir; Raoda Tul Jannah Maruddani; Rika Wati (LP2M IAIN Sultan Amai Gorontalo, 2025)
This study aims to determine the effectiveness of using storytelling aprons in stimulating the speaking abilities of 4–5-year-old children with speech delays at the Pembina Muaro Jambi State Kindergarten. The background of this study is based on the importance of early language stimulation, especially for children with speech delays, so that their language and social development can develop optimally. This study employs the Classroom Action Research (CAR) method following the Kemmis and Taggart model, conducted over three cycles. Each cycle consists of planning, implementing actions, observation, and reflection. The results indicate that the use of storytelling aprons has a positive impact on improving the speech abilities of children with speech delays. There was an increase in the average score from 48.3% in cycle I to 86% in cycle III. This medium proved to be effective in stimulating children to develop storytelling skills, letter pronunciation, and number recognition. Thus, the storytelling apron can be used as an effective learning alternative to support language development in children with speech delays